Analysis of Alternative Splicing During the Combinatorial Response to Simultaneous Copper and Iron Deficiency in Arabidopsis Reveals Differential Events in Genes Involved in Amino Acid Metabolism - Mancini, Estefania; Garcia-Molina, Antoni (Frontiers in Plant Science, 2022)
Copper (Cu) and iron (Fe) constitute fundamental nutrients for plant biology but are often limited due to low bioavailability. Unlike responses to single Cu or Fe deprivation, the consequences of simultaneous Cu and Fe deficiency have not yet been fully deciphered. Previously, it was demonstrated that Cu and Fe deficiency applied in combination imposes transcriptome, proteome, and metabolome changes different from those triggered under each deficiency individually. Here, we evaluated the effect of alternative splicing (AS) on the transcriptome of rosette leaves under single and simultaneous Cu and Fe deficiency. Differentially spliced genes (DSGs) and differentially expressed genes (DEGs) coincided in number (2,600 approx.) although the overlapping fraction was minimal (15%). Functional annotation of changes exclusively detected under simultaneous Cu and Fe deficiency revealed that DEGs participated in general stress responses and translation, while DSGs were involved in metabolic reactions, especially amino acid biosynthesis. Interestingly, transcripts encoding central features for tryptophan (Trp) and asparagine (Asn) synthesis – two significantly altered metabolites under simultaneous Cu and Fe deficiency – underwent exclusive intron retention events under the double deficiency. However, transcript and protein amounts for these enzymes did not correlate with Trp and Asn concentration. In consequence, we propose that AS might act as a regulatory mechanism to modify the stability and/or functionality of the enzymes and therefore fine-tune amino acid production during the combinatorial response to simultaneous Cu and Fe deficiency.